1998
DOI: 10.1146/annurev.arplant.49.1.173
|View full text |Cite
|
Sign up to set email alerts
|

ELABORATION OF BODY PLAN AND PHASE CHANGE DURING DEVELOPMENT OF ACETABULARIA: How Is the Complex Architecture of a Giant Unicell Built?

Abstract: While uninucleate and unicellular, Acetabularia acetabulum establishes and maintains functionally and morphologically distinct body regions and executes phase changes like those in vascular plants. Centimeters tall at maturity, this species has allowed unusual experimental approaches. Amputations revealed fates of nucleate and enucleate portions from both wild type and mutants. Historically, graft chimeras between nucleate and enucleate portions suggested that morphological instructions were supplied by the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 88 publications
0
35
0
1
Order By: Relevance
“…The most well-known species of this type are in the genus Acetabularia (an ulvophyte) that is famous for transplantation experiments demonstrating nuclear control over cell morphology (Mandoli 1998;Mine et al 2008). …”
Section: Giant Uninucleate Algaementioning
confidence: 99%
“…The most well-known species of this type are in the genus Acetabularia (an ulvophyte) that is famous for transplantation experiments demonstrating nuclear control over cell morphology (Mandoli 1998;Mine et al 2008). …”
Section: Giant Uninucleate Algaementioning
confidence: 99%
“…Transplant experiments with the giant-celled Acetabularia, conducted by Joachim Hämmerling, demonstrated that the nucleus of a cell contains the genetic information that directs cellular development, and postulated the existence of messenger RNA before its structure was determined (Hämmerling, 1953). Acetabularia, along with other giant-celled green algae (Valonia, Chara and Nitella), has also served as an experimental organism for electro-physiological research and studies of cell morphogenesis (Menzel, 1994;Mandoli, 1998;Shepherd et al, 2004;Bisson et al, 2006;Mine et al, 2008). The charophyte Mougeotia played a key role in outlining the role of phytochrome in plant development (Winands & Wagner, 1996).…”
mentioning
confidence: 99%
“…Plastid and nuclear genomes of C. reinhardtii are readily transformed (Debuchy et al, 1989;Kindle et al, 1989;Diener et al, 1990;Mayfield and Kindle, 1990;Shimogawara et al, 1998) using any of a number of different selectable markers (Debuchy et al, 1989;Fernandez et al, 1989;Kindle, 1990;GoldschmidtClermont, 1991;Nelson et al, 1994;Stevens et al, 1996;Lumbreras et al, 1998;Auchincloss et al, 1999;Kovar et al, 2002). Plasmid, cosmid, and bacterial artificial chromosome libraries (Purton and Rochaix, 1994;Zhang et al, 1994;Lefebvre and Silflow, 1999) al., 1998;Wykoff et al, 1998) or E. coli Palombella and Dutcher, 1998) mutant strains. Methods have been developed for generating tagged mutant alleles (Tam and Lefebvre, 1993;Davies et al, 1994Davies et al, , 1996Smith and Lefebvre, 1996;Koutoulis et al, 1997;Smith and Lefebvre, 1997;Zhang and Lefebvre, 1997;Asleson and Lefebvre, 1998;Davies et al, 1999;Wykoff et al, 1999), and alleles not tagged can be isolated by map-based cloning (Vysotskaia et al, 2001;Kathir et al, 2003).…”
Section: Reinhardtiimentioning
confidence: 99%
“…It is an organism that can readily be used to study those transcripts generated in the nucleus (which is located in the cell rhizoid) and transmitted/accumulated in more distal locations of the cell where they control biological processes. Developmental studies concerning Acetabularia have recently been discussed (Mandoli, 1998), and a comparison of cDNAs from the juvenile and adult stage has been initiated (Henry et al, 2004). An equally interesting organism is Caulerpa.…”
Section: A Brief View Of Specific Organisms That Might Be Considered mentioning
confidence: 99%
See 1 more Smart Citation